IMF Programs and Financial Flows to Offshore Centers - Aiyar, Shekhar (IMF Working Papers; Working Paper ;, 2021)
This paper examines whether IMF lending is associated with increases in outflows to offshore financial centers (OFCs), known for bank secrecy and asset protection, relative to other international destinations. Using quarterly data from the BIS on bilateral bank deposits, we are unable to detect any positive and statistically significant effect of IMF loan disbursements on bank deposits in OFCs. The result holds even after restricting the sample to the duration of the IMF program, where disbursement quarters and non-disbursement quarters should be subject to similar degrees of macroeconomic stress. It is also robust to using the scheduled tranche of disbursements as an instrument for actual disbursements. While the effects vary by the type and conditionality of the IMF program, as well as the amount of lending, none of the effects are found to be positive and statistically significant. We also estimate whether the recent surge in emergency lending, during the Covid-19 crisis, is associated with an increase in outflows to OFCs but find no evidence to support this.